Urethane prepolymers, adhesives, patches, adhesive tapes, wearable devices, and wearable device kits

A urethane prepolymer-based adhesive with controlled adhesion properties addresses the challenge of maintaining high moisture permeability and low skin adhesion for wearable devices, ensuring strong attachment without skin damage.

JP7616047B2Active Publication Date: 2025-01-17AGC INC

Patent Information

Application Number
JP2021501991
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-02-28
Filing Date
2020-02-17
Publication Date
2025-01-17
Estimated Expiration
2040-02-17

AI Technical Summary

Technical Problem

Adhesives used for attaching wearable devices to the skin require both high moisture permeability and low adhesion to the skin to prevent damage during removal, while maintaining strong adhesion to the device body.

Method used

A urethane prepolymer is formulated using oxyalkylene polymers with specific hydroxyl group and ethylene oxide unit contents, combined with a polyisocyanate compound to create an adhesive with controlled adhesion properties, achieving low skin adhesion and high base material adhesion.

Benefits of technology

The adhesive exhibits excellent moisture permeability and balanced adhesion, minimizing skin damage and ensuring strong attachment to wearable devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007616047000001
    Figure 0007616047000001
  • Figure 0007616047000002
    Figure 0007616047000002
  • Figure 0007616047000003
    Figure 0007616047000003
Patent Text Reader

Abstract

To provide a urethane prepolymer that can be used to obtain an adhesive that has excellent moisture permeability and that is both low adhesion to the skin and high adhesion to a substrate, as well as an adhesive, a patch, an adhesive tape, a wearable device, and a wearable device kit. A hydroxyl-terminated urethane prepolymer, an adhesive, a patch, an adhesive tape, a wearable device, and a wearable device kit, which is a hydroxyl-terminated urethane prepolymer obtained by reacting an oxyalkylene polymer A having an average number of 2.1 to 3 hydroxyl groups per molecule, an oxyalkylene polymer B having one hydroxyl group per molecule, and a diisocyanate compound, wherein the number average molecular weight of the oxyalkylene polymer B is 5,000 or more, and the ethylene oxide unit content in the hydroxyl-terminated urethane prepolymer exceeds 10% by mass.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a urethane prepolymer, an adhesive, an adhesive patch, an adhesive tape, a wearable device, and a wearable device kit. [Background technology]

[0002] An adhesive to be applied to the skin is required to have excellent moisture permeability so that, when used as an adhesive layer of an adhesive patch, moisture generated by sweat from the skin can evaporate to the outside of the patch.

[0003] Patent Document 1 states that the moisture permeability is 5000 g / m 2 The document describes a polyurethane-based adhesive for skin application for 10 days or more, which is obtained by reacting (1) a polyol containing a polyoxyalkylene structure with a number average molecular weight of 5,000 or more and an average functionality of 2 or more, (2) a polyol containing a polyoxyalkylene structure with a number average molecular weight of 1,500-5,000 and an average functionality of 1, and (3) an organic polyisocyanate. The average functionality of all polyols used to obtain the adhesive is 2-2.6, and the content of ethylene oxide units in all polyols in the adhesive is 3-8% by weight.

[0004] Furthermore, in recent years, adhesives have begun to be used to attach wearable devices to the skin, and while high adhesion to the wearable device itself is required, low adhesion to the skin is also required so as not to damage the skin when the wearable device is removed from the skin. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 5457446 Summary of the Invention [Problem to be solved by the invention]

[0006] Adhesives to be applied to the skin are required to have excellent moisture permeability, as well as low adhesion to the skin and high adhesion to the substrate. However, the adhesive described in Patent Document 1 has high adhesive strength to both the skin and the base material, and when the adhesive is applied to the skin, there is a risk that the skin may be damaged when the adhesive is peeled off from the skin.

[0007] Therefore, an object of the present invention is to provide a urethane prepolymer that can provide an adhesive that has excellent moisture permeability and that achieves both low adhesion to the skin and high adhesion to a substrate, as well as a pressure-sensitive adhesive, a patch, an adhesive tape, a wearable device, and a wearable device kit. [Means for solving the problem]

[0008] The above problem is solved by the following configuration. [1] A hydroxyl-terminated urethane prepolymer obtained by reacting an oxyalkylene polymer A having an average number of hydroxyl groups per molecule of 2.1 to 3, an oxyalkylene polymer B having a hydroxyl group per molecule of 1, and a diisocyanate compound, The number average molecular weight of the oxyalkylene polymer B is 5000 or more, The hydroxyl-terminated urethane prepolymer has an ethylene oxide unit content of more than 10 mass%. [2] The hydroxyl-terminated urethane prepolymer according to [1], wherein the oxyalkylene polymer B has a number average molecular weight of more than 5,000. [3] The hydroxyl-terminated urethane prepolymer according to [1] or [2], wherein the oxyalkylene polymer A comprises an oxyalkylene polymer a having 3 hydroxyl groups per molecule and an oxyalkylene polymer b having 2 hydroxyl groups per molecule. [4] The hydroxyl group-terminated urethane prepolymer according to [3], wherein the oxyalkylene polymer a has an ethylene oxide unit content of 15 mass% or more. [5] The hydroxyl group-terminated urethane prepolymer according to any one of [1] to [4], having an average number of hydroxyl groups of less than 3.0. [6] The hydroxyl-terminated urethane prepolymer according to any one of [1] to [5], wherein the ethylene oxide unit content in the hydroxyl-terminated urethane prepolymer is 12 to 50 mass%. [7] A pressure-sensitive adhesive obtained by reacting the hydroxyl-terminated urethane prepolymer according to any one of [1] to [6] with a curing agent containing a polyisocyanate compound having three or more isocyanate groups in one molecule, The ethylene oxide unit content in the pressure-sensitive adhesive is 10% by mass or more. Adhesive. [8] A pressure-sensitive adhesive obtained by reacting an oxyalkylene polymer A having an average number of hydroxyl groups per molecule of 2.1 to 3, an oxyalkylene polymer B having a hydroxyl group per molecule of 1, and a polyisocyanate compound, The number average molecular weight of the oxyalkylene polymer B is 5000 or more, The ethylene oxide unit content in the pressure-sensitive adhesive is 10% by mass or more. Adhesive. [9] The pressure-sensitive adhesive described in [8], wherein the number average molecular weight of the oxyalkylene polymer B is greater than 5,000.

[10] The pressure-sensitive adhesive described in [8] or [9], wherein the oxyalkylene polymer A contains an oxyalkylene polymer a having 3 hydroxyl groups per molecule and an oxyalkylene polymer b having 2 hydroxyl groups per molecule.

[11] The pressure-sensitive adhesive according to

[10] , wherein the oxyalkylene polymer a has an ethylene oxide unit content of 15 mass% or more.

[12] The pressure-sensitive adhesive according to any one of [8] to

[11] , wherein the pressure-sensitive adhesive has an ethylene oxide unit content of 12 to 50 mass %.

[13] The storage modulus at 80°C is 4.0×10 5 The pressure-sensitive adhesive according to any one of [8] to

[12] , wherein the pressure-sensitive adhesive has a viscosity of not more than 1 Pa.

[14] Moisture permeability of 3000g / m 2 The adhesive according to any one of [8] to

[13] , wherein the adhesive is applied for 10 days or more.

[15] The adhesive according to any one of [8] to

[14] , which has an adhesive strength to human skin of 0.2 to 1 N / 15 mm.

[16] The adhesive according to any one of [8] to

[15] , wherein the difference between the adhesive strength to phenolic resin and the adhesive strength to human skin is 2 N / 15 mm or more.

[17] A substrate; A patch comprising: an adhesive layer provided on the surface of the base material, the adhesive layer comprising the adhesive according to any one of [8] to

[16] .

[18] A substrate; An adhesive tape comprising: an adhesive layer provided on at least one surface of the substrate, the adhesive layer comprising the adhesive according to any one of [8] to

[16] .

[19] A wearable device body; A wearable device comprising: an adhesive layer provided on at least a part of an adhesion surface of the wearable device body, the adhesive layer comprising the adhesive according to any one of [8] to

[16] .

[20] A wearable device body; A wearable device kit comprising: an adhesive according to any one of [8] to

[16] ; and a patch according to

[17] or an adhesive tape according to

[18] , for attaching the wearable device body to the skin. Effect of the Invention

[0009] The present invention can provide a urethane prepolymer that can provide an adhesive that has excellent moisture permeability and that achieves both low adhesion to the skin and high adhesion to a substrate, as well as an adhesive, a patch, an adhesive tape, a wearable device, and a wearable device kit. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] In this specification, the definitions and meanings of terms are as follows. An "oxyalkylene polymer" is a polymer having a polyoxyalkylene chain. A repeating unit based on an alkylene oxide is called an "alkylene oxide unit." "Hydroxyl-terminated urethane prepolymer" refers to a compound obtained by reacting an organic compound having a hydroxyl group with a diisocyanate compound, which has a hydroxyl group at at least a part of the molecular chain terminal and a urethane bond in the molecular chain. In addition, in this specification, "isocyanate-terminated urethane prepolymer" refers to a compound obtained by reacting an organic compound having two or more hydroxyl groups in one molecule with a polyisocyanate compound, which has an isocyanate group at at least a part of the molecular chain terminal and a urethane bond in the molecular chain. The number average molecular weight (hereinafter referred to as "Mn") and molecular weight distribution (hereinafter referred to as "Mw / Mn") of the oxyalkylene polymer are values ​​obtained by measurement according to the method described below. As standard samples for molecular weight measurement, several kinds of monodisperse polypropylene glycol polymers with different polymerization degrees are measured using a commercially available GPC measuring device (HLC-8320GPC, manufactured by Tosoh Corporation), and a calibration curve is created based on the relationship between the molecular weight of polypropylene glycol and retention time. The oxyalkylene polymer, which is the measurement sample, is diluted to 0.5% by mass with tetrahydrofuran, passed through a 0.5 μm filter, and then the measurement sample is measured using the above-mentioned GPC measuring device. The GPC spectrum of the measurement sample is analyzed by computer using the above-mentioned calibration curve, and the Mn and mass average molecular weight (hereinafter referred to as Mw) of the measurement sample are obtained. The molecular weight distribution is Mw divided by Mn. The degree of unsaturation of the oxyalkylene polymer is a value measured according to the method of JIS-K1557-6. The hydroxyl value of the oxyalkylene polymer is a value measured and calculated according to the titration method of JIS K 0070:1992 "Testing methods for acid value, saponification value, ester value, iodine value, hydroxyl value and unsaponifiable matter of chemical products".

[0011] [Hydroxyl-terminated urethane prepolymer] The hydroxyl-terminated urethane prepolymer of the present invention is obtained by reacting an oxyalkylene polymer A, an oxyalkylene polymer B, and a diisocyanate compound. The hydroxyl groups of the oxyalkylene polymer A and the oxyalkylene polymer B react with the isocyanate groups of the diisocyanate compound to form urethane bonds between the oxyalkylene polymer A and the oxyalkylene polymer B and the diisocyanate compound. Of the hydroxyl groups of the oxyalkylene polymer A and the oxyalkylene polymer B, the hydroxyl groups remaining unreacted with the isocyanate groups of the diisocyanate compound become hydroxyl groups at the ends of the molecular chains of the urethane prepolymer.

[0012] <Oxyalkylene polymer A> The oxyalkylene polymer A (hereinafter also referred to as polymer A) is an oxyalkylene polymer having an average number of 2.1 to 3 hydroxyl groups per molecule.

[0013] The average number of hydroxyl groups per molecule of the oxyalkylene polymer A is not particularly limited as long as it is 2.1 to 3, but is more preferably 2.2 to 2.8. When the average number of hydroxyl groups is within the above range, the moisture permeability is excellent, and it is easy to achieve both low adhesion to the skin and high adhesion to the substrate. When the average number of hydroxyl groups of the oxyalkylene polymer A is within the range of 2.1 to 3, the adhesive strength of the resulting adhesive to the skin and to the substrate is easily within an appropriate range, and adhesive residue when peeled off from the skin is small, which is preferable. The adhesive residue means that the adhesive remains on the skin when the adhesive is attached to the skin and then peeled off.

[0014] The average number of hydroxyl groups per molecule of the oxyalkylene polymer A is 13 The amount was calculated by identifying the type and molar ratio of the initiator using C-NMR (nuclear magnetic resonance). 13 In C-NMR analysis, characteristic peaks of the initiator are observed, and the type and molar ratio of the initiator can be identified from the peak position and peak area. Usually, the number of hydroxyl groups per molecule of an oxyalkylene polymer is equal to the number of hydroxyl groups per molecule of an initiator used in synthesizing the oxyalkylene polymer. When an oxyalkylene polymer is synthesized using, for example, glycerin as an initiator, an oxyalkylene polymer having 3 hydroxyl groups per molecule is usually obtained. When an oxyalkylene polymer is synthesized using, for example, pentaerythritol as an initiator, an oxyalkylene polymer having 4 hydroxyl groups per molecule is usually obtained. When an oxyalkylene polymer is synthesized using, for example, dipropylene glycol as an initiator, an oxyalkylene polymer having 2 hydroxyl groups per molecule is usually obtained. The average number of hydroxyl groups per molecule of the oxyalkylene polymer A is calculated from the number of hydroxyl groups per molecule based on the type of initiator and the molar fraction of the initiator. For example, when glycerin is 30 mol% and dipropylene glycol is 70 mol%, the average number of hydroxyl groups is 3×0.3+2×0.7=2.3.

[0015] The alkylene oxide used in synthesizing the oxyalkylene polymer A is not particularly limited, but is preferably an alkylene oxide having 2 to 5 carbon atoms, more preferably one or more selected from ethylene oxide and propylene oxide, and even more preferably propylene oxide alone or a combination of ethylene oxide and propylene oxide. In the case of using propylene oxide and ethylene oxide in combination, the arrangement of the ethylene oxide units and the propylene oxide units may be random or in blocks. When ethylene oxide and an alkylene oxide other than ethylene oxide are used in combination as the alkylene oxide, the molar ratio of ethylene oxide to the alkylene oxide other than ethylene oxide is not particularly limited, but is preferably such that the ethylene oxide unit content of the oxyalkylene polymer A falls within the range described below. The higher the ethylene oxide unit content, the more improved the hydrophilicity of the oxyalkylene polymer A, and the lower the ethylene oxide unit content, the more likely the crystallinity of the oxyalkylene polymer A is to decrease.

[0016] The ethylene oxide unit content of the oxyalkylene polymer A is not particularly limited, but is preferably 0 to 80 mass%, more preferably 0 to 60 mass%, further preferably 5 to 55 mass%, and even more preferably 12 to 50 mass%. When the ethylene oxide unit content of the oxyalkylene polymer A is within this range, the oxyalkylene polymer A tends to be amorphous, making it easy to handle, and the adhesive obtained has more appropriate adhesion to the skin.

[0017] The ethylene oxide unit content of the oxyalkylene polymer A is 13 It is calculated by determining the monomer composition of the oxyalkylene chain using C-NMR. For example, when the oxyalkylene polymer A is a polyol consisting of propylene oxide units and ethylene oxide units, the ethylene oxide unit content can be determined from the area ratio of the signal of the methyl group in the propylene oxide unit to the signals of the methylene groups in the propylene oxide unit and the ethylene oxide unit.

[0018] The Mn of the oxyalkylene polymer A is not particularly limited, but is preferably 1000 to 50000, more preferably 5000 to 30000. When the Mn of the oxyalkylene polymer A is within this range, the flexibility of the resulting adhesive is better. In addition, the adhesive strength and adhesive residue of the resulting adhesive are more appropriate. When two or more kinds of oxyalkylene polymers A are contained, it is preferable that the Mn, Mw / Mn, degree of unsaturation and average number of functional groups of each of the oxyalkylene polymers A are within the above-mentioned ranges.

[0019] The oxyalkylene polymer A preferably contains an oxyalkylene polymer a (hereinafter referred to as "polymer a") having 3 hydroxyl groups per molecule, and an oxyalkylene polymer b (hereinafter referred to as "polymer b") having 2 hydroxyl groups per molecule. When the oxyalkylene polymer A contains both the polymer a and the polymer b, the adhesive strength to the skin and the adhesive strength to a substrate are more easily kept within an appropriate range.

[0020] The polymer a may be of two or more types. The ethylene oxide unit content of the polymer a is not particularly limited, but is preferably 0% by mass or more, more preferably 10 to 80% by mass, even more preferably 15 to 60% by mass, and even more preferably 15 to 30% by mass. When two or more types of polymer a are contained, the ethylene oxide unit content calculated as a weighted average of the ethylene oxide unit contents is preferably within the above range. Furthermore, Mn of the polymer a is not particularly limited, but is preferably from 1000 to 50000, more preferably from 5000 to 30000, and further preferably from 8000 to 25000. When two or more types of polymer a are contained, Mn of each of the polymers a is preferably within the above range. The Mw / Mn of the polymer a is not particularly limited, but is preferably less than 1.20, more preferably less than 1.13, and particularly preferably less than 1.10. By making the molecular weight distribution of the polymer a less than 1.20, the reactivity tends to be good, the urethane prepolymer described below can be produced more efficiently, and the viscosity of the obtained urethane prepolymer tends to be reduced. The degree of unsaturation of the polymer a is preferably 0.015 meq / g or less, more preferably 0.013 meq / g or less, and even more preferably 0.008 meq / g or less. The degree of unsaturation of the oxyalkylene polymer a may be zero. If the degree of unsaturation of the polymer a is equal to or less than the upper limit, the curing property of the obtained prepolymer is better, and the adhesive residue on the skin is further reduced. When two or more kinds of oxyalkylene polymers a are contained, it is preferable that the Mn, Mw / Mn and degree of unsaturation of each of the polymers a are within the above ranges.

[0021] The polymer b may be of two or more types. The ethylene oxide unit content of the polymer b is not particularly limited, but is preferably 0% by mass or more, more preferably 10 to 80% by mass or more, even more preferably 15 to 60% by mass, and even more preferably 15 to 30% by mass. When two or more types of polymer b are contained, the ethylene oxide unit content calculated as a weighted average of the ethylene oxide unit contents is preferably within the above range. Furthermore, Mn of the oxyalkylene polymer b is not particularly limited, but is preferably from 1000 to 50000, more preferably from 5000 to 30000, and further preferably from 8000 to 25000. When two or more kinds of polymers b are contained, Mn of each of the polymers b is preferably within the above range. The Mw / Mn of the polymer b is not particularly limited, but is preferably less than 1.20, more preferably less than 1.13, and particularly preferably less than 1.10. By making the molecular weight distribution of the oxyalkylene polymer a less than 1.20, the reactivity tends to be good, the urethane prepolymer described below can be produced more efficiently, and the viscosity of the obtained urethane prepolymer tends to be reduced. The degree of unsaturation of the polymer b is preferably 0.015 meq / g or less, more preferably 0.013 meq / g or less, and even more preferably 0.008 meq / g or less. The degree of unsaturation of the oxyalkylene polymer b may be zero. If the degree of unsaturation of the polymer b is equal to or less than the upper limit, the curing property of the obtained prepolymer is better, and the adhesive residue on the skin is further reduced. When two or more kinds of polymers b are contained, it is preferable that the Mn, Mw / Mn and degree of unsaturation of each of the polymers b are within the above ranges.

[0022] The content ratio of polymer a to the total mass of polymer a and polymer b is not particularly limited, but is preferably 5 to 95 mass%, more preferably 10 to 80 mass%, and even more preferably 15 to 60 mass%. When the content ratio of polymer a to the total mass of polymer a and polymer b is within this range, it is preferable because the adhesive residue when peeled off from the skin is small.

[0023] The ratio of the polymer a to the polymer b contained in the oxyalkylene polymer A can be calculated as follows. The hydroxyl value of the oxyalkylene polymer A is calculated according to the titration method of JIS K 0070:1992 "Testing methods for acid value, saponification value, ester value, iodine value, hydroxyl value and unsaponifiable matter of chemical products". In addition, the number average molecular weight of the oxyalkylene polymer A converted into an oxyalkylene polymer is calculated by measuring GPC and analyzing using a calibration curve obtained using the oxyalkylene polymer as the standard substance. The hydroxyl value and Mn obtained as above are substituted into the formula "(hydroxyl value×Mn) / 56100" to calculate the average number of hydroxyl groups. Next, 13 The type of initiator contained in the oxyalkylene polymer A is identified by confirming, for example, the presence or absence of a tertiary carbon derived from glycerin using C-NMR, and the proportion of units derived from each initiator is calculated from the information on the average number of functional groups and the type of initiator, thereby calculating the proportion of polymer a and polymer b contained in the oxyalkylene polymer A.

[0024] As long as the average number of hydroxyl groups per molecule is 2.1 to 3, the oxyalkylene polymer A may contain an oxyalkylene polymer other than the polymer a, the polymer b, and the oxyalkylene polymer B. Examples of such oxyalkylene polymers other than the oxyalkylene polymer a, the oxyalkylene polymer b, and the oxyalkylene polymer B include an oxyalkylene polymer having 4 or more hydroxyl groups per molecule and an oxyalkylene polymer having an Mn of less than 5,000 and having 1 hydroxyl group per molecule. The total mass proportion of the polymer a and the polymer b in the oxyalkylene polymer A is preferably 80 mass % or more, more preferably 90 mass % or more, and even more preferably 100 mass %.

[0025] The method for producing the oxyalkylene polymer A is not particularly limited, but examples thereof include a method in which a polymer a having 3 hydroxyl groups per molecule and a polymer b having 2 hydroxyl groups per molecule are separately synthesized and then mixed, and a method in which the oxyalkylene polymer A is synthesized as a mixture of a polymer a having 3 hydroxyl groups per molecule and a polymer b having 2 hydroxyl groups per molecule.

[0026] In order to synthesize the oxyalkylene polymer A, it is preferable to subject an alkylene oxide to a ring-opening addition reaction in the presence of a catalyst to an initiator having two or more hydroxyl groups in one molecule.

[0027] To synthesize polymer b, an initiator having two hydroxyl groups in one molecule is used. As the initiator having two hydroxyl groups in one molecule for synthesizing polymer b, one or more selected from the group consisting of ethylene glycol, diethylene glycol, propylene glycol, and dipropylene glycol are preferred, one or more selected from propylene glycol and dipropylene glycol are more preferred, and propylene glycol is even more preferred. Propylene glycol is available at low cost, and can reduce the synthesis cost of polymer b.

[0028] To synthesize the polymer a, an initiator having three hydroxyl groups in one molecule is used. As an initiator for synthesizing the polymer a, glycerin is preferred. Glycerin is available at low cost, and can reduce the synthesis cost of the oxyalkylene polymer a.

[0029] An initiator having four or more hydroxyl groups in one molecule is used to synthesize an oxyalkylene polymer having four or more hydroxyl groups per molecule, which may be contained in the oxyalkylene polymer A. Examples of initiators having four or more hydroxyl groups in one molecule include, but are not limited to, polyhydric alcohols having 4 or more hydroxyl groups, such as diglycerin, pentaerythritol, dipentaerythritol, and tripentaerythritol, and sugars or derivatives thereof, such as glucose, sorbitol, dextrose, fructose, sucrose, and methyl glucoside.

[0030] To synthesize an oxyalkylene polymer having one hydroxyl group per molecule that may be contained in the oxyalkylene polymer A, an initiator having one hydroxyl group per molecule is used. The initiator having one hydroxyl group per molecule is the same as the initiator that can be used when synthesizing the oxyalkylene polymer B described below. However, the Mn of the oxyalkylene polymer having one hydroxyl group per molecule that may be contained in the oxyalkylene polymer A is less than 5,000.

[0031] To synthesize the oxyalkylene polymer A as a mixture of oxyalkylene polymers having different numbers of hydroxyl groups per molecule, a mixture of initiators having different numbers of hydroxyl groups per molecule is used. However, the type and amount of the initiator used are set so that the average number of hydroxyl groups in the obtained oxyalkylene polymer is 2.1 to 3.

[0032] The alkylene oxide used in synthesizing the polymer a, the polymer b, the oxyalkylene polymer having 4 or more hydroxyl groups per molecule, and the oxyalkylene polymer having an Mn of less than 5,000 and having 1 hydroxyl group per molecule is the same as the alkylene oxide used in synthesizing the oxyalkylene polymer A described above.

[0033] A catalyst for ring-opening addition polymerization of an alkylene oxide to an initiator can be a conventionally known catalyst, such as an alkali catalyst like KOH, a transition metal compound-porphyrin complex catalyst like a complex obtained by reacting an organoaluminum compound with porphyrin, a composite metal cyanide complex catalyst, or a catalyst made of a phosphazene compound. When the oxyalkylene polymer A is obtained using a composite metal cyanide complex catalyst, the molecular weight distribution of the obtained oxyalkylene polymer A can be narrowed, and it is preferable to obtain an oxyalkylene polymer A having a low viscosity. The composite metal cyanide complex may be a conventionally known compound, and the method for producing a polymer using the composite metal cyanide complex may be a conventionally known method. For example, the compounds and production methods disclosed in International Publication No. 2003 / 062301, International Publication No. 2004 / 067633, JP-A-2004-269776, JP-A-2005-015786, International Publication No. 2013 / 065802, JP-A-2015-010162, etc. may be used. A conventionally known method can be used for subjecting an alkylene oxide to a ring-opening addition polymerization to an initiator to obtain an oxyalkylene polymer A. For example, the production methods disclosed in International Publication No. 2011 / 125951, Japanese Patent No. 5648797, etc. can be used.

[0034] <Oxyalkylene polymer B> The oxyalkylene polymer B is an oxyalkylene polymer having one hydroxyl group per molecule and an Mn of at least 5000. The Mn of the oxyalkylene polymer B is preferably more than 5000.

[0035] The number of hydroxyl groups per molecule of oxyalkylene polymer B is 1. The number of hydroxyl groups of oxyalkylene polymer B is 13 It can be measured using C-NMR. 13 The type of initiator can be identified from the peaks obtained by C-NMR. If the initiator has one hydroxyl group per molecule, it can be determined that the number of hydroxyl groups is one.

[0036] The oxyalkylene polymer B has a structure in which one or more alkylene oxides are added by ring-opening to an initiator having one hydroxyl group in one molecule. The number of carbon atoms of the alkylene oxide is not particularly limited, but is preferably 2 to 5, and more preferably 2 to 3. When two or more kinds of alkylene oxides are subjected to ring-opening addition to an initiator, the arrangement of units derived from each alkylene oxide may be random or block. As the alkylene oxide, it is preferable to use propylene oxide alone or to use propylene oxide and ethylene oxide in combination. When propylene oxide and ethylene oxide are used in combination, the molar ratio of propylene oxide to ethylene oxide is not particularly limited, but it is preferable to set the ethylene oxide unit content of the oxyalkylene polymer B within the range described below. The higher the propylene oxide unit content, the lower the crystallinity of the oxyalkylene polymer B, and the higher the ethylene oxide unit content, the more the hydrophilicity of the oxyalkylene polymer B tends to be improved.

[0037] The oxyalkylene polymer B may be of two or more types. The ethylene oxide unit content of the oxyalkylene polymer B is not particularly limited, but is preferably 0 to 80 mass%, more preferably 0 to 60 mass%, further preferably 5 to 55 mass%, and even more preferably 10 to 50 mass%. When the ethylene oxide unit content of the oxyalkylene polymer B is within this range, the adhesive to the skin and moisture permeability of the obtained pressure-sensitive adhesive become more appropriate. The ethylene oxide unit content of the oxyalkylene polymer B can be calculated in the same manner as for the oxyalkylene polymer A. When two or more kinds of oxyalkylene polymers B are contained, the ethylene oxide unit content, calculated as a weighted average thereof, is preferably within the above range.

[0038] The Mn of the oxyalkylene polymer B is not particularly limited as long as it is 5000 or more, but is preferably 5000 to 50000, more preferably more than 5000 and not more than 50000, and even more preferably 8000 to 30000. When the Mn of the oxyalkylene polymer B is 5000 or more, the flexibility of the obtained adhesive and the conformability to the skin when applied to the skin are improved. When the Mn of the oxyalkylene polymer B is more than 5000, the flexibility of the obtained adhesive is further improved. In addition, the conformability to the skin when the obtained adhesive is applied to the skin is further improved. The Mw / Mn of the oxyalkylene polymer B is not particularly limited, but is preferably less than 1.20, more preferably less than 1.13, and particularly preferably less than 1.10. By making the molecular weight distribution of the oxyalkylene polymer B less than 1.20, the reactivity tends to be good, the urethane prepolymer described below can be produced more efficiently, and the viscosity of the obtained urethane prepolymer tends to be reduced. The degree of unsaturation of the oxyalkylene polymer B is preferably 0.015 meq / g or less, more preferably 0.013 meq / g or less, and even more preferably 0.008 meq / g or less. The degree of unsaturation of the oxyalkylene polymer B may be zero. If the degree of unsaturation of the oxyalkylene polymer B is equal to or less than the upper limit, the curing property of the obtained prepolymer is better, and the adhesive residue on the skin is further reduced. The Mn of the oxyalkylene polymer B can be measured in the same manner as that of the oxyalkylene polymer A. When two or more kinds of oxyalkylene polymers B are contained, it is preferable that the Mn, Mw / Mn and degree of unsaturation of each of the oxyalkylene polymers B are within the above ranges.

[0039] In order to synthesize the oxyalkylene polymer B, it is preferable to subject an alkylene oxide to a ring-opening addition reaction in the presence of a catalyst to an initiator having one hydroxyl group per molecule. As the initiator having one hydroxyl group in one molecule for synthesizing the oxyalkylene polymer B, a monohydric alcohol having 2 to 4 carbon atoms is preferred, more preferably at least one selected from the group consisting of propanol (n-propyl alcohol), 2-propanol (isopropyl alcohol), 1-butanol (n-butyl alcohol), 2-butanol (sec-butyl alcohol), 2-methyl-1-propanol (isobutyl alcohol) and 2-methyl-2-propanol (tert-butyl alcohol), and even more preferably at least one selected from the group consisting of 1-butanol (n-butyl alcohol), 2-butanol (sec-butyl alcohol), 2-methyl-1-propanol (isobutyl alcohol) and 2-methyl-2-propanol (tert-butyl alcohol). Alcohols having 2 to 4 carbon atoms are available at low cost, and the synthesis cost of the oxyalkylene polymer B can be reduced.

[0040] As the catalyst, it is preferable to use a DMC catalyst, as in the case of the oxyalkylene polymer A. However, since the Mn of the oxyalkylene polymer B is 5000 or more, the reaction conditions such as the reaction time are adjusted so that the Mn of the oxyalkylene polymer to be synthesized is 5000 or more.

[0041] <Diisocyanate compounds> The diisocyanate compound used to obtain the hydroxyl-terminated urethane prepolymer of the present invention by reacting with the oxyalkylene polymer A and the oxyalkylene polymer B is not particularly limited as long as it is an organic compound having two isocyanate groups in one molecule.

[0042] The diisocyanate compound may be at least one selected from the group consisting of an aliphatic diisocyanate compound, an alicyclic diisocyanate compound, an aromatic diisocyanate compound, and an araliphatic diisocyanate compound.

[0043] Examples of the aliphatic diisocyanate compound include linear aliphatic diisocyanates such as tetramethylene diisocyanate, dodecamethylene diisocyanate, and hexamethylene diisocyanate (HDI), and branched aliphatic diisocyanates such as 2,2,4-trimethylhexamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, lysine diisocyanate, 2-methylpentane-1,5-diisocyanate, and 3-methylpentane-1,5-diisocyanate, but are not limited thereto. As the aliphatic diisocyanate compound, linear aliphatic diisocyanates are preferred, linear aliphatic diisocyanates having 4 to 8 carbon atoms are more preferred, and hexamethylene diisocyanate (HDI) is even more preferred, because the glass transition temperature of the resulting polyurethane (adhesive) is higher and the tensile strength and elongation at break are more excellent.

[0044] Examples of alicyclic diisocyanate compounds include, but are not limited to, isophorone diisocyanate, hydrogenated xylylene diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, 1,4-cyclohexane diisocyanate, methylcyclohexylene diisocyanate, and 1,3-bis(isocyanatomethyl)cyclohexane. As the alicyclic diisocyanate compound, either one or both of isophorone diisocyanate and 4,4'-dicyclohexylmethane diisocyanate are preferred, and isophorone diisocyanate is more preferred, in that the glass transition temperature of the resulting polyurethane (adhesive) is higher and the tensile strength and elongation at break are more excellent.

[0045] Examples of aromatic diisocyanate compounds include, but are not limited to, tolylene diisocyanate (TDI), 2,2'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate (MDI), 4,4'-dibenzyl diisocyanate, 1,5-naphthylene diisocyanate, xylylene diisocyanate, 1,3-phenylene diisocyanate, and 1,4-phenylene diisocyanate. As the aromatic diisocyanate compound, diphenylmethane diisocyanate is preferred, and 4,4'-diphenylmethane diisocyanate (MDI) is more preferred, since the glass transition temperature of the resulting polyurethane is higher.

[0046] Examples of the aromatic aliphatic diisocyanate compound include, but are not limited to, dialkyldiphenylmethane diisocyanate, tetraalkyldiphenylmethane diisocyanate, and α,α,α,α-tetramethylxylylene diisocyanate. As the aromatic aliphatic diisocyanate compound, α,α,α,α-tetramethylxylylene diisocyanate is preferred because the resulting polyurethane has a better elongation at break.

[0047] The diisocyanate compound used in producing the hydroxyl-terminated urethane prepolymer of the present invention is, from the viewpoint of providing a polyurethane with superior tensile strength and elongation at break, preferably one or more selected from the group consisting of aliphatic diisocyanate compounds and alicyclic diisocyanate compounds, more preferably an aliphatic diisocyanate compound, even more preferably an aliphatic diisocyanate compound having 4 to 6 carbon atoms, still more preferably one or more selected from the group consisting of HDI and modified products thereof, and even more preferably HDI or an isocyanurate modified product of HDI.

[0048] As the diisocyanate compound for producing the hydroxyl group-terminated urethane prepolymer of the present invention, a bifunctional isocyanate group-terminated urethane prepolymer obtained by prepolymerizing the above-mentioned aliphatic diisocyanate compound, alicyclic diisocyanate compound, aromatic diisocyanate compound or araliphatic diisocyanate compound with a diol may be used. Examples of diols for producing an isocyanate group-terminated urethane prepolymer include, but are not limited to, ethylene glycol, propylene glycol, 1,4-butanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, and 1,6-hexanediol. As the diol, one or more selected from the group consisting of ethylene glycol, propylene glycol, 1,4-butanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, and 1,6-hexanediol are preferred, and propylene glycol is more preferred, in that the glass transition temperature of the resulting polyurethane (adhesive) is higher. The isocyanate index when producing an isocyanate group-terminated urethane prepolymer is made to exceed 100. The isocyanate index is the value obtained by dividing the number of moles of isocyanate groups in a diisocyanate compound by the number of moles of hydroxyl groups in a diol and multiplying the result by 100. Commercially available difunctional isocyanate group-terminated urethane prepolymers include, for example, Duranate D101, Duranate D201, and Duranate A201H (all manufactured by Asahi Kasei Corporation), but are not limited thereto.

[0049] <Method of producing hydroxyl-terminated urethane prepolymer> The method for producing the hydroxyl-terminated urethane prepolymer of the present invention is not particularly limited, but examples thereof include a method in which oxyalkylene polymer A and oxyalkylene polymer B are reacted with a diisocyanate compound in a ratio such that the isocyanate index is less than 100. The isocyanate index is a value obtained by dividing the number of moles of isocyanate groups in the diisocyanate compound by the total number of moles of hydroxyl groups in oxyalkylene polymer A and oxyalkylene polymer B and multiplying the result by 100. The content ratio of oxyalkylene polymer A to the total mass of oxyalkylene polymer A and oxyalkylene polymer B is not particularly limited, but is preferably 10 to 95 mass%, more preferably 20 to 80 mass%. When the content ratio of oxyalkylene polymer A to the total mass of oxyalkylene polymer A and oxyalkylene polymer B is within this range, the resulting pressure-sensitive adhesive can maintain a better balance between the permeability and the adhesiveness to the skin and the substrate. The average number of hydroxyl groups in the hydroxyl-terminated urethane prepolymer is preferably less than 3.0, more preferably 1.7 to 2.9, even more preferably 1.7 to 2.5, and particularly preferably 1.8 to 2.4. When the average number of hydroxyl groups in the hydroxyl-terminated urethane prepolymer is within this range, the resulting pressure-sensitive adhesive can maintain a better balance between the permeability and the adhesion to the skin and the substrate. The "average number of hydroxyl groups, f" of the hydroxyl-terminated urethane prepolymer is a value obtained by the following formula (I). f=(1000f n / Mn) / [{(1000 / Mn)-(unsaturation degree / f n )}+degree of unsaturation] ···(I) However, f n is the number of active hydrogen atoms per molecule of the initiator used as a raw material in producing the oxyalkylene polymer. In addition, when multiple oxyalkylene polymers are used in combination, the "average number of functional groups f ave " can be calculated according to the following formula (II). f ave =Σ(f i ×W i / Mn i ) / Σ(W i / Mn i ) (II) However, f i is the number of active hydrogen atoms per molecule of the initiator used as a raw material in each oxyalkylene polymer, W i is the mass part of each oxyalkylene polymer, Mn i represents Mn in each oxyalkylene polymer.

[0050] In the production of the hydroxyl-terminated urethane prepolymer of the present invention, a catalyst can be used, if necessary. The catalyst used is preferably one or more selected from tertiary amine compounds and organometallic compounds. Examples of tertiary amine compounds include, but are not limited to, triethylamine, triethylenediamine, and 1,8-diazabicyclo(5,4,0)-undecene-7 (DBU). The organometallic compound is preferably at least one selected from tin-based compounds and non-tin-based compounds. Examples of tin compounds include, but are not limited to, dibutyltin dichloride, dibutyltin oxide, dibutyltin dibromide, dibutyltin dimaleate, dibutyltin dilaurate (DBTDL), dibutyltin diacetate, dibutyltin sulfide, tributyltin sulfide, tributyltin oxide, tributyltin acetate, triethyltin ethoxide, tributyltin ethoxide, dioctyltin oxide, tributyltin chloride, tributyltin trichloroacetate, and tin 2-ethylhexanoate. Examples of non-tin-based compounds include titanium-based compounds such as dibutyltitanium dichloride, tetrabutyltitanium trichloride, and butoxytitanium trichloride; lead-based compounds such as lead oleate, lead 2-ethylhexanoate, lead benzoate, and lead naphthenate; iron-based compounds such as iron 2-ethylhexanoate and iron acetylacetonate; cobalt-based compounds such as cobalt benzoate and cobalt 2-ethylhexanoate; zinc-based compounds such as zinc naphthenate and zinc 2-ethylhexanoate; and zirconium-based compounds such as zirconium naphthenate. The catalyst may be used alone or in combination of two or more. When a catalyst is used, the amount of the catalyst used is not particularly limited, but is preferably 0.01 to 1.0 part by mass per 100 parts by mass of the total of the oxyalkylene polymer A, the oxyalkylene polymer B, and the diisocyanate compound.

[0051] In the production of the hydroxyl-terminated urethane prepolymer of the present invention, a solvent can be used as necessary. The solvent is preferably one or more selected from ketones such as acetone and methyl ethyl ketone, esters such as ethyl acetate, and aromatic hydrocarbons such as toluene and xylene. The solvents may be used in combination of two or more kinds. When a solvent is used, the amount of the solvent used is not particularly limited, but is preferably 50 to 500 parts by mass per 100 parts by mass of the total of the oxyalkylene polymer and the diisocyanate compound.

[0052] Examples of methods for producing the hydroxyl-terminated urethane prepolymer of the present invention include the following methods. Production method 1: A method in which a diisocyanate compound, an oxyalkylene polymer A, an oxyalkylene polymer B, a catalyst, and a solvent are all charged into a flask at once. Production method 2: A method in which oxyalkylene polymer A, oxyalkylene polymer B, a catalyst and a solvent are charged in a flask, and a diisocyanate compound is added dropwise thereto. Among these methods, production method 2 is preferred because it allows the low molecular weight components in the raw material to react preferentially, narrows the molecular weight distribution, and makes it easier to control the reaction.

[0053] The reaction temperature is preferably less than 100° C., more preferably from 85 to 95° C. When the reaction temperature is less than 100° C., side reactions other than the urethane reaction are easily suppressed, making it easier to obtain the desired prepolymer.

[0054] The isocyanate index when producing the hydroxyl-terminated urethane prepolymer of the present invention is preferably 30 to 95, more preferably 40 to 95, and even more preferably 50 to 95. When the isocyanate index is within this range, a hydroxyl-terminated urethane prepolymer having an appropriate molecular chain length can be produced, thereby further improving productivity.

[0055] After the reaction is completed, it is preferable to add a reaction terminator to inactivate the catalyst. Examples of reaction terminators include, but are not limited to, acetylacetone. Two or more reaction terminators may be used in combination.

[0056] <Ethylene oxide unit content in hydroxyl-terminated urethane prepolymer> The ethylene oxide unit content in the hydroxyl-terminated urethane prepolymer of the present invention is 10% by mass or more, preferably 10 to 80% by mass, and more preferably 12 to 50% by mass. When the ethylene oxide unit content in the hydroxyl-terminated urethane prepolymer of the present invention is 10% by mass or more, the resulting pressure-sensitive adhesive can achieve both low adhesion to skin and high adhesion to a substrate.

[0057] [Adhesive] The pressure-sensitive adhesive of the present invention is an adhesive having an ethylene oxide unit content of 10% by mass or more, which is obtained by reacting an oxyalkylene polymer A having an average number of 2.1 to 3 hydroxyl groups per molecule with an oxyalkylene polymer B having one hydroxyl group per molecule and a number average molecular weight of 5,000 or more with a polyisocyanate compound, or an adhesive obtained by reacting the hydroxyl-terminated urethane prepolymer of the present invention with a curing agent (hereinafter sometimes simply referred to as "curing agent") containing a polyisocyanate compound having three or more isocyanate groups per molecule. The polyisocyanate compound is a compound having two or more isocyanate groups in one molecule, and refers to the above-mentioned diisocyanate compound and the below-mentioned polyisocyanate compound having three or more isocyanate groups in one molecule.

[0058] The ethylene oxide unit content in the adhesive of the present invention is 10% by mass or more, preferably 10 to 80% by mass, and more preferably 12 to 50% by mass. When the ethylene oxide unit content in the adhesive of the present invention is 10% by mass or more, the moisture permeability becomes better, the adhesiveness to a highly polar substrate is further improved, and the stratum corneum is less likely to peel off in a wet state. The storage modulus of the pressure-sensitive adhesive of the present invention at 25° C. is 1.0×10 4 Pa~5.0×10 5 Pa is preferred, 2.0×10 4 Pa~4.8×10 5 Pa is more preferable, 2.0×10 4 Pa~3.0×10 5 Pa is more preferable, and 2.0×10 4 Pa~2.5×10 5 Pa is particularly preferred, and 2.0×10 4 Pa~1.0×10 5 The storage modulus of the pressure-sensitive adhesive of the present invention within the above range is most preferably Pa. When the pressure-sensitive adhesive of the present invention has a storage modulus within the above range, the adhesiveness to the skin is improved, adhesive residue is less likely to be left, and better skin adhesive strength is obtained. The storage modulus of the pressure-sensitive adhesive of the present invention at 80° C. is 4.0×10 5 Pa or less is preferable, and 5.0×10 2 Pa or more 3.0×10 5 Pa or less is preferable, and 1.0×10 3 Pa ~ 6.0 × 10 4 Pa is more preferable, and 1.0×10 3 Pa ~ 4.0 × 10 4 Pa is more preferable, and 2.0×10 3 Pa~1.0×10 4 Particularly preferred is Pa. When the storage modulus of the pressure-sensitive adhesive of the present invention is within the above range, the adhesiveness to the skin is improved, adhesive residue is less likely to be left, and better skin adhesive strength is obtained.

[0059] <Adhesive manufacturing method> A method for producing a pressure-sensitive adhesive by reacting the hydroxyl-terminated urethane prepolymer of the present invention with a curing agent will now be described.

[0060] The curing agent may contain a polyisocyanate compound having three or more isocyanate groups in one molecule, as well as a polyisocyanate compound having two isocyanate groups in one molecule (diisocyanate compound). Examples of the diisocyanate compound include the diisocyanate compound and the bifunctional isocyanate group-terminated urethane prepolymer. Examples of the polyisocyanate compound having three or more isocyanate groups in one molecule include the isocyanurate modified product of the diisocyanate compound, the biuret modified product of the diisocyanate compound, the allophanate modified product of the diisocyanate compound, and the trifunctional or higher isocyanate group-terminated urethane prepolymer (adduct modified product) obtained by reacting the diisocyanate compound with a polyol having three or more hydroxyl groups in one molecule. Examples of the isocyanurate modified product include Coronate HX (manufactured by Tosoh Corporation). Examples of the biuret modified product include Duranate 24A-100 (manufactured by Asahi Kasei Corporation). Examples of commercially available tri- or higher functional isocyanate group-terminated urethane prepolymers include, but are not limited to, Coronate L, Coronate L-55E, and Coronate L-45E (all manufactured by Tosoh Corporation).

[0061] The isocyanate index when the pressure-sensitive adhesive of the present invention is produced by reacting a hydroxyl-terminated urethane prepolymer with a curing agent is more than 100, and more preferably from 105 to 160. The isocyanate index is a value obtained by dividing the number of moles of isocyanate groups in the curing agent by the number of moles of hydroxyl groups in the hydroxyl-terminated urethane prepolymer and multiplying the result by 100.

[0062] When the pressure-sensitive adhesive of the present invention is produced by reacting the hydroxyl-terminated urethane prepolymer with the curing agent, a catalyst can be used as necessary. The type of catalyst is preferably the catalyst described above. The amount of catalyst used is preferably 0.01 to 1.0 parts by mass per 100 parts by mass of the total of the hydroxyl-terminated urethane prepolymer and the curing agent. After the reaction is completed, it is preferable to add a reaction terminator to inactivate the catalyst.

[0063] When the pressure-sensitive adhesive of the present invention is produced by reacting the hydroxyl-terminated urethane prepolymer with the curing agent, a solvent can be used as necessary. The type of the solvent is preferably the above-mentioned solvent. The amount of the solvent used is preferably 50 to 500 parts by mass per 100 parts by mass of the total of the hydroxyl-terminated urethane prepolymer and the curing agent.

[0064] The temperature when reacting the hydroxyl group-terminated urethane prepolymer with the curing agent is preferably less than 100°C, and more preferably from 85 to 95°C.

[0065] A method for producing a pressure-sensitive adhesive by reacting the above-mentioned oxyalkylene polymer A, the above-mentioned oxyalkylene polymer B, and a polyisocyanate compound will be described.

[0066] In this production method, the polyisocyanate compound can be selected from a polyisocyanate compound having two isocyanate groups in one molecule and a polyisocyanate compound having three or more isocyanate groups in one molecule. For example, one or more of the diisocyanate compounds and the polyisocyanate compounds usable as the curing agent can be used as the polyisocyanate compound to be reacted with the oxyalkylene polymer A and the oxyalkylene polymer B.

[0067] The isocyanate index in this production method is more than 100, and more preferably from 105 to 160. The isocyanate index is a value obtained by dividing the number of moles of isocyanate groups in a polyisocyanate compound by the total number of moles of hydroxyl groups in oxyalkylene polymer A and oxyalkylene polymer B and multiplying the result by 100.

[0068] When the pressure-sensitive adhesive of the present invention is produced by reacting the oxyalkylene polymer A, the oxyalkylene polymer B, and the polyisocyanate compound, a catalyst may be used as necessary. The type of catalyst is preferably the catalyst described above. The amount of catalyst used is preferably 0.01 to 1.0 part by mass per 100 parts by mass of the total of the oxyalkylene polymer A, the oxyalkylene polymer B, and the polyisocyanate compound. After the reaction is completed, it is preferable to add a reaction terminator to inactivate the catalyst.

[0069] When the pressure-sensitive adhesive of the present invention is produced by reacting the oxyalkylene polymer A, the oxyalkylene polymer B, and the polyisocyanate compound, a solvent can be used as necessary. The type of the solvent is preferably the above-mentioned solvent. The amount of the solvent used is preferably 50 to 500 parts by mass per 100 parts by mass of the total of the oxyalkylene polymer A, the oxyalkylene polymer B, and the polyisocyanate compound.

[0070] The temperature when the oxyalkylene polymer A and the oxyalkylene polymer B are reacted with the polyisocyanate compound is preferably less than 100°C, more preferably from 85 to 95°C.

[0071] <Ingredients that may be added to the adhesive> The pressure-sensitive adhesive of the present invention may further contain one or more of various additives such as a plasticizer, an antioxidant, an antistatic agent, a filler, an ultraviolet absorber, a light stabilizer, and a leveling agent.

[0072] The plasticizer is not particularly limited, but from the viewpoint of compatibility with other components, fatty acid esters or phosphate esters having 8 to 30 carbon atoms are preferable. When the pressure-sensitive adhesive of the present invention contains a plasticizer, the wettability of the pressure-sensitive adhesive to the adherend is further improved. Examples of fatty acid esters having 8 to 30 carbon atoms include esters of monobasic acids or polybasic acids having 6 to 18 carbon atoms and branched alcohols having 18 or less carbon atoms, esters of unsaturated fatty acids or branched acids having 14 to 18 carbon atoms and tetrahydric or less alcohols, esters of monobasic acids or polybasic acids having 6 to 18 carbon atoms and polyalkylene glycols, and fatty acid esters in which the unsaturated site has been epoxidized with a peroxide or the like.

[0073] Examples of the phosphate ester include ester compounds of phosphorous acid or phosphoric acid and a linear or branched alcohol having 2 to 18 carbon atoms.

[0074] The antioxidant is not particularly limited, but is preferably a phenol-based antioxidant, an amine-based antioxidant, a sulfur-based antioxidant, or a phosphorus-based antioxidant, and is more preferably a phenol-based antioxidant in terms of low skin sensitization. When the pressure-sensitive adhesive of the present invention contains an antioxidant, thermal deterioration of the pressure-sensitive adhesive can be suppressed.

[0075] Specific examples of the phenol-based antioxidant include monophenol-based antioxidants such as 2,6-di-t-butyl-p-cresol, bisphenol-based antioxidants such as 2,2'-methylenebis(4-methyl-6-t-butylphenol), and polymeric phenol-based antioxidants such as 1,1,3-tris(2-methyl-4-hydroxy-5-t-butylphenyl)butane.

[0076] Specific examples of amine-based antioxidants include bis(2,2,6,6-tetramethyl-4-piperidyl)sebacate, a polycondensate of dimethyl succinate and 1-(2-hydroxyethyl)-4-hydroxy-2,2,6,6-tetramethylpiperidineethanol, N,N',N'',N'''-tetrakis-(4,6-bis-(butyl-(N-methyl-2,2,6,6-tetramethylpiperidin-4-yl)amino)-triazin-2-yl)-4,7-diazadecane-1,10-diamine, and a polycondensate of dibutylamine·1,3,5-triazine·N,N'-bis(2,2,6,6-tetramethyl-4-piperidyl)-1,6-hexamethylenediamine and N-(2,2,6,6-tetramethyl-4-piperidyl)butylamine.

[0077] Specific examples of the sulfur-based antioxidant include dilauryl 3,3'-thiodipropionate, dimyristyl 3,3'-thiodipropionate, and distearyl 3,3'-thiodipropionate. Specific examples of the phosphorus-based antioxidant include triphenyl phosphite, diphenyl isodecyl phosphite, and phenyl diisodecyl phosphite.

[0078] The antistatic agent is not particularly limited, and examples thereof include inorganic salts, ionic liquids, and surfactants. When the pressure-sensitive adhesive of the present invention contains an antistatic agent, it suppresses electrostatic discharge, and for example, it is easy to prevent damage to electronic components and the like incorporated in a wearable device. Examples of inorganic salts include sodium chloride, potassium chloride, lithium chloride, lithium perchlorate, ammonium chloride, potassium chlorate, aluminum chloride, copper chloride, ferrous chloride, ferric chloride, ammonium sulfate, potassium nitrate, sodium nitrate, sodium carbonate, and sodium thiocyanate. The ionic liquid is a salt of a cation and an anion, and the cation is preferably, for example, an imidazolium ion, a pyridinium ion, or an ammonium ion. Examples of the surfactant include nonionic surfactants such as glycerin fatty acid esters, anionic surfactants such as alkylsulfonates, cationic surfactants such as tetraalkylammonium salts, and amphoteric surfactants.

[0079] Fillers include, for example, talc, calcium carbonate, and titanium oxide.

[0080] Examples of the ultraviolet absorber include benzophenone-based ultraviolet absorbers, benzotriazole-based ultraviolet absorbers, salicylic acid-based ultraviolet absorbers, anilide oxalate-based ultraviolet absorbers, cyanoacrylate-based ultraviolet absorbers, and triazine-based ultraviolet absorbers.

[0081] Examples of the light stabilizer include hindered amine light stabilizers and ultraviolet light stabilizers. Examples of the hindered amine light stabilizer include, but are not limited to, bis(2,2,6,6-tetramethyl-4-piperidyl)sebacate, bis(1,2,2,6,6-pentamethyl-4-piperidyl)sebacate, and methyl 1,2,2,6,6-pentamethyl-4-piperidylsebacate. Examples of the ultraviolet stabilizer include, but are not limited to, nickel bis(octylphenyl)sulfide, [2,2'-thiobis(4-tert-octylphenolate)]-n-butylamine nickel, nickel complex-3,5-di-tert-butyl-4-hydroxybenzyl-phosphate monoethylate, nickel-dibutyldithiocarbamate, benzoate type quenchers, and nickel-dibutyldithiocarbamate.

[0082] <Moisture permeability> The moisture permeability of the adhesive of the present invention is 3000 g / m 2 ·day or more is preferable, 3500g / m 2 ·day or more is preferable, 4000g / m 2 The upper limit of the moisture permeability is not particularly limited. The moisture permeability of the adhesive of the present invention is measured by measuring the moisture permeability of 1 m2 Calculate the amount per day. The test specimens are prepared as follows. A hydroxyl-terminated urethane prepolymer or oxyalkylene polymer A and oxyalkylene polymer B are mixed with a curing agent, and applied to a polyester film (release body, thickness 50 μm) that has been subjected to a release treatment using a knife coater so that the dry film thickness is 25 μm, and then the film is cured and dried for 3 minutes at 100° C. to form an adhesive layer on the release body. A coarse nylon net that does not affect the moisture permeability of the adhesive is attached to the obtained adhesive layer, and the film is stored in a hot air dryer in an atmosphere of 50° C. for 3 days to complete the crosslinking reaction of the adhesive layer, and the release body is peeled off to prepare a test piece. The moisture permeability was measured in an atmosphere of 40°C, with the relative humidity of one side of the space separated by the test piece at 90% and the other side of the space kept dry with a moisture absorbent. The mass (g) of water vapor passing through the test piece in 24 hours (1 day) was measured. 2 The measurement is carried out according to JIS Z 0208:1976 Moisture permeability test method for moisture-proof packaging materials (cup method), and a circular test piece with a diameter about 10 mm larger than the inside diameter of the cup is placed over a cup containing about 50 g of calcium chloride moisture absorbent, and then a rubber packing and ring are placed over the test piece and screwed in place to prevent it from slipping. After measuring the total mass of this test piece, it is placed in a constant temperature and humidity chamber at 40°C and 90% RH, and the change in mass is measured at regular intervals, and the moisture permeability is calculated according to the following formula. Moisture permeability (g / m 2 ·day)=W×240000 / S where S is the moisture permeability area (cm 2 ) and W represents the mass gain per hour (g / hr).

[0083] <Adhesive strength to phenolic resin> The adhesive strength of the pressure-sensitive adhesive of the present invention to phenolic resin is preferably 2.5 N / 15 mm or more, and more preferably 3 N / 15 mm or more. The adhesive strength of the pressure-sensitive adhesive of the present invention to phenolic resin is the adhesive strength obtained by adhering a 15 mm wide test piece to a Bakelite panel (phenolic resin plate, manufactured by Sumitomo Bakelite Co., Ltd., PL-1102) in an atmosphere of 25°C, pressing it back and forth once at a speed of 300 mm / min with a 2 kg rubber roll, leaving it for 20 minutes, and then measuring the peel force at a peel angle of 90 degrees or 180 degrees and a peel speed of 300 mm / min, according to the test method described in "10. Adhesive strength" of the test method for adhesive tapes and adhesive sheets of JIS Z 0237:2009.

[0084] <Adhesion to human skin> The adhesive strength of the pressure-sensitive adhesive of the present invention to human skin is preferably 0.2 to 1 N / 15 mm, more preferably 0.3 to 0.7 N / 15 mm. The adhesive strength of the adhesive of the present invention to human skin is the adhesive strength obtained by measuring the adhesive strength to phenolic resin using the back of a human hand instead of a Bakelite panel in the above-mentioned method for measuring the adhesive strength to phenolic resin. The back of the human hand is degreased with isopropyl alcohol and air-dried before use.

[0085] <Difference in adhesive strength between phenolic resin and human skin> The difference between the adhesive strength of the adhesive of the present invention to phenol resin and to human skin is preferably 2 N / 15 mm or more, more preferably 2.5 N / 15 mm or more. The difference in adhesive strength between the phenolic resin and the human skin was calculated using the following formula. "Difference between adhesive strength to phenolic resin and adhesive strength to human skin" = "Adhesive strength to phenolic resin" - "Adhesive strength to human skin"

[0086] [Two-component adhesive] The pressure-sensitive adhesive of the present invention may be a two-component pressure-sensitive adhesive comprising a first part containing the hydroxyl-terminated urethane prepolymer of the present invention and a second part containing a polyisocyanate compound having three or more isocyanate groups in one molecule. By mixing the first and second parts, the formation of urethane bonds proceeds, and a pressure-sensitive adhesive containing polyurethane is obtained. The second agent containing the polyisocyanate compound having three or more isocyanate groups in one molecule is the same as the above-mentioned curing agent. The first or second agent may further contain a catalyst, a solvent, the above-mentioned components that may be blended in the pressure-sensitive adhesive, and the like. The first and second agents are contained in separate containers, which may be various containers such as tubes and bottles. The sales form of the two-component adhesive of the present invention may be a form containing a first agent and a second agent, or a form containing a first agent but not a second agent. In a sales form not containing a second agent, the user can use a curing agent prepared separately, which increases the user's flexibility.

[0087] [Adhesive material] The patch of the present invention comprises a substrate and an adhesive layer provided on the surface of the substrate, the adhesive layer comprising the adhesive of the present invention. The patch of the present invention preferably has a configuration in which a pressure-sensitive adhesive layer is provided on one surface of a base film, and a release liner is releasably laminated to cover the adhesive surface of the pressure-sensitive adhesive layer.

[0088] The thickness of the base film is not particularly limited, but is preferably 1 to 9 μm, more preferably 3 to 9 μm. When the thickness of the base film is within this range, the possibility of the patch breaking can be reduced, and the patch can be secured to follow the skin surface. The material of the base film is not particularly limited, but examples thereof include urethane-based polymers such as polyether urethane and polyester urethane, amide-based polymers such as polyether polyamide block polymers, acrylic polymers such as polyacrylate, olefin-based polymers such as polyethylene, polypropylene, and ethylene / vinyl acetate copolymer, and ester-based polymers such as polyether polyester. As the material of the base film, urethane-based polymers or amide-based polymers are preferred from the viewpoint of moisture permeability. The material of the base film can be used alone or in combination of two or more. Furthermore, a laminated film in which base films manufactured from different materials are laminated may be used. The base film can be laminated with a cloth such as a woven fabric, a nonwoven fabric, a knitted fabric, or a net. The thickness of the adhesive layer is not particularly limited, but is preferably 10 to 50 μm, more preferably 15 to 35 μm. When the thickness of the adhesive layer is within this range, the adhesive layer will have better adhesion to the skin surface.

[0089] In order to prevent the surface of the adhesive layer from being contaminated, the adhesive layer of the adhesive material of the present invention is preferably covered with a release liner until use. This release liner can be one generally used for skin or adhesive tapes to be applied to skin. Specifically, it can be a release liner that is coated with a release agent having release properties such as silicone resin or fluororesin on the surface of high-quality paper, glassine paper, parchment paper, etc., or a release agent having release properties such as silicone resin or fluororesin on the surface of high-quality paper anchor-coated with resin or high-quality paper laminated with polyethylene, etc., can be used.

[0090] In the patch of the present invention, a carrier film can be peelably laminated on the surface of the base film opposite to the surface on which the adhesive layer is formed. The material of the carrier film is not particularly limited, but plastic film and paper are preferred. In particular, a transparent plastic film can be attached to the skin while the application site is seen through the patch, and therefore its usefulness is particularly remarkable when fixing a medical instrument such as a catheter. In order to peelably attach the carrier film to the back surface of the base film, a method such as inflation molding, extrusion lamination molding, lamination molding, or casting can be used. The thickness of the carrier film varies depending on the material, but is usually preferably about 15 to 200 μm, more preferably about 20 to 100 μm.

[0091] [Adhesive tape] The pressure-sensitive adhesive tape of the present invention has a substrate and a pressure-sensitive adhesive layer provided on at least one surface of the substrate, the pressure-sensitive adhesive layer comprising the pressure-sensitive adhesive of the present invention. In the pressure-sensitive adhesive tape of the present invention, the pressure-sensitive adhesive layer may be provided on only one surface of the substrate, or on both surfaces of the substrate.

[0092] One embodiment of the pressure-sensitive adhesive tape of the present invention preferably has a pressure-sensitive adhesive layer provided on one side of a base film, and a release liner releasably laminated to cover the adhesive side of the pressure-sensitive adhesive layer. This embodiment is particularly called a single-sided pressure-sensitive adhesive tape. The base film and release liner are the same as those in the patch of the present invention, and the thickness of the adhesive layer is the same as that of the adhesive layer in the patch of the present invention. This form of adhesive tape can be used to fix an article to the skin surface by covering at least a portion of the article to be fixed to the skin surface with the adhesive tape.

[0093] Another embodiment of the pressure-sensitive adhesive tape of the present invention preferably has pressure-sensitive adhesive layers on both sides of a base film and a release liner releasably laminated to cover the pressure-sensitive adhesive surface of the pressure-sensitive adhesive layer. This embodiment is particularly called a double-sided pressure-sensitive adhesive tape. The base film and release liner are the same as those in the patch of the present invention, and the thickness of the adhesive layer is the same as that of the adhesive layer in the patch of the present invention. This form of adhesive tape can be used to fix an article to the skin surface, with the adhesive tape being interposed between at least a portion of the part of the article to be fixed to the skin surface that comes into contact with the skin surface and the skin surface.

[0094] In still another embodiment of the pressure-sensitive adhesive tape of the present invention, a pressure-sensitive adhesive layer is provided on one surface of a releasable base film, and a release liner is preferably provided releasably covering the adhesive surface of the pressure-sensitive adhesive layer, and this embodiment is particularly referred to as a pressure-sensitive adhesive transfer tape. The peelable base film is preferably a base film usable for the patch of the present invention, the surface of which is coated with a release agent having peeling properties, such as silicone resin or fluororesin. The release liner is the same as that of the patch of the present invention. The thickness of the adhesive layer is the same as that of the adhesive layer in the patch of the present invention. This form of adhesive tape can be used to fix an article to the skin surface, with the adhesive layer being interposed between the skin surface and at least a part of the part of the article to be fixed to the skin surface that comes into contact with the skin surface. Since only the adhesive layer is interposed between the article to be fixed to the skin surface and the skin surface, and no base film is present, the adhesion between the article and the skin surface can be improved.

[0095] [Wearable devices, wearable device kits] The wearable device of the present invention has a wearable device body and an adhesive layer containing the adhesive of the present invention provided on at least a part of the adhesion surface of the wearable device body. In addition, the wearable device kit of the present invention includes a wearable device main body and the adhesive of the present invention, the patch of the present invention, or the adhesive tape of the present invention for attaching the wearable device main body to the skin of a mammal.

[0096] Examples of wearable devices include, but are not limited to, sensors for heart rate, heart rate variability, heart rate interval, heart rate waveform, cardiac potential, electromyographic activity, activity level, blood pressure, body surface temperature, brain waves, brain wave interval, or respiratory interval.

[0097] The thickness of the adhesive layer provided on at least a part of the adhesion surface of the wearable device body is not particularly limited, but is preferably 10 to 50 μm, more preferably 15 to 40 μm. When the thickness of the adhesive layer is within this range, the wearable device body is less likely to fall off when attached to the skin, and the attachment surface is less likely to be damaged when peeled off from the skin.

[0098] The wearable device main body can also be attached to the skin using the patch of the present invention or the adhesive tape of the present invention. The wearable device can be attached to the skin by sandwiching the wearable device body between the patch and the skin. When the adhesive tape is a single-sided adhesive tape, the wearable device can be attached to the skin by sandwiching the wearable device body between the adhesive tape and the skin. When the adhesive tape is double-sided tape, the wearable device can be attached to the skin with the adhesive tape interposed between the wearable device body and the skin. If the adhesive tape is an adhesive transfer tape, an adhesive layer can be transferred to at least a portion of the adhesion surface of the wearable device body, and the wearable device can be attached to the skin with only the adhesive layer between the wearable device body and the skin. The skin is preferably a mammalian skin, more preferably a terrestrial mammalian skin, even more preferably a human skin, which may include the labial mucosa. EXAMPLES

[0099] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples, and various modifications are possible without departing from the gist of the present invention.

[0100] [Synthesis of oxyalkylene polymer] (Synthesis Example 1: Synthesis of Polymer A1) Glycerin was used as the initiator. First, 1000 g of initiator and TBA-DMC catalyst slurry were charged into a pressure-resistant reactor to prepare a reaction liquid. The amount of TBA-DMC catalyst slurry charged was set so that the metal concentration of the TBA-DMC catalyst in the reaction liquid was 46 ppm. Next, the atmosphere inside the pressure-resistant reaction vessel was replaced with nitrogen, and the reaction liquid was heated with stirring. When the temperature reached 135°C, heating was stopped, and while continuing to stir, 120 g of propylene oxide (12 parts by mass per 100 parts by mass of initiator) was supplied into the pressure-resistant reaction vessel and reacted. After the temperature rise of the reaction solution had stopped, it was cooled to 135°C, and while stirring the reaction solution, 4728 g of propylene oxide was fed into the pressure-resistant reactor. After it was confirmed that the internal pressure had stopped changing and the reaction had ended, the catalyst was neutralized and removed using a synthetic adsorbent (Kyowado 600S, manufactured by Kyowa Chemical Industry Co., Ltd.). The number of hydroxyl groups, hydroxyl value, Mn, Mw / Mn, degree of unsaturation, and content of oxyethylene units (hereinafter referred to as "EO units") of the polymer A1 thus obtained are shown in Table 1. These values ​​were measured by the above-mentioned method. The same is shown for the polymers obtained in the following synthesis examples in Table 1.

[0101] (Synthesis Example 2: Synthesis of Polymer A2) Polymer A2 was synthesized in the same manner as in Synthesis Example 1, except that 20 mass % of propylene oxide was changed to ethylene oxide.

[0102] (Synthesis Example 3: Synthesis of Polymer A3) Polymer A3 was synthesized in the same manner as in Synthesis Example 1, except that 80 mass % of propylene oxide was changed to ethylene oxide.

[0103] (Synthesis Example 4: Synthesis of Polymer A4) Polymer A4 was synthesized in the same manner as in Synthesis Example 1, except that the initiator was changed from glycerin to propylene glycol.

[0104] (Synthesis Example 5: Synthesis of Polymer A5) Polymer A5 was synthesized in the same manner as in Synthesis Example 2, except that the initiator was changed from glycerin to propylene glycol.

[0105] (Synthesis Example 6: Synthesis of Polymer B1) Polymer B1 was synthesized in the same manner as in Synthesis Example 1, except that the initiator was changed from glycerin to 1-butanol.

[0106] (Synthesis Example 7: Synthesis of Polymer B2) Polymer B2 was synthesized in the same manner as in Synthesis Example 2, except that the initiator was changed from glycerin to 1-butanol.

[0107] [Table 1]

[0108] <Hydroxyl value> The hydroxyl value of oxyalkylene polymer A is calculated according to the titration method of JIS K 0070:1992 "Testing methods for acid value, saponification value, ester value, iodine value, hydroxyl value and unsaponifiable matter of chemical products."

[0109] <Production of Hydroxyl-Terminated Urethane Prepolymer> [Production Example 1] As shown in Table 2, 30 parts by mass of polymer A1, 70 parts by mass of polymer A4, toluene and 100 parts by mass of ethyl acetate were added to a reaction vessel equipped with a thermometer, a stirrer and a cooling tube. Next, 0.03 parts by mass of a urethane catalyst (dibutyltin dilaurate, manufactured by Tokyo Chemical Industry Co., Ltd.) was added and mixed at 40°C, and then 1.51 parts by mass of hexamethylene diisocyanate (Duranate 50M, manufactured by Asahi Kasei Corporation, referred to as "HDI" in Table 1) was added as a diisocyanate compound and reacted at 80°C. The isocyanate index was 80. Heat was generated by the reaction, the internal temperature rose to about 80°C, and the viscosity also increased over time. The mixture was reacted for 7 hours at 80°C while adding ethyl acetate at appropriate times to dilute the mixture, and a hydroxyl-terminated urethane prepolymer (also referred to as "urethane prepolymer U1") having an average hydroxyl number of 2.3 was obtained as a uniform and transparent liquid.

[0110] [Production Example 2] As shown in Table 2, a hydroxyl-terminated urethane prepolymer having an average number of hydroxyl groups of 2.1 (also referred to as "urethane prepolymer U2") was produced in the same manner as in Production Example 1, except that 30 parts by mass of polymer A2, 40 parts by mass of polymer A5, and 30 parts by mass of polymer B1 were used instead of polymers A1 and A4, and 5.00 parts by mass of D201 (isocyanate-terminated urethane prepolymer, manufactured by Asahi Kasei Corporation) was used as the diisocyanate compound. [Production Example 3] As shown in Table 2, a hydroxyl-terminated urethane prepolymer (also referred to as "urethane prepolymer U3") having an average hydroxyl group number of 2.0 was produced in the same manner as in Production Example 2, except that 30 parts by mass of polymer B2 was used instead of polymer B1, and 4.91 parts by mass of D201 was used as the diisocyanate compound. [Production Example 4] As shown in Table 2, a hydroxyl-terminated urethane prepolymer (also referred to as "urethane prepolymer U4") having an average hydroxyl group number of 1.9 was produced in the same manner as in Production Example 3, except that 30 parts by mass of polymer A3 was used instead of polymer A2, and 4.77 parts by mass of D201 was used as the diisocyanate compound.

[0111] <Adhesive manufacturing> [Example 1] As shown in Table 3, 100 parts by mass of urethane prepolymer U1 and 2 parts by mass of a curing agent (Coronate L, Tosoh Corporation product name) were uniformly mixed and degassed, and the mixture was applied to a release-treated polyester film (release body, thickness 50 μm) using a knife coater to a dry film thickness of 25 μm, and then cured and dried for 3 minutes at 100° C. A 38 μm-thick polyester film (support) was attached to the obtained adhesive layer, and the mixture was stored in a hot air dryer in an atmosphere of 50° C. for 3 days to complete the crosslinking reaction of the adhesive layer, thereby producing an adhesive. The ethylene oxide unit content in the resulting pressure sensitive adhesive was 0 mass %.

[0112] [Example 2] A pressure-sensitive adhesive was produced in the same manner as in Example 1, except that urethane prepolymer U2 was used instead of urethane prepolymer U1 as shown in Table 3. The ethylene oxide unit content in the resulting pressure-sensitive adhesive was 14 mass%.

[0113] [Example 3] As shown in Table 3, urethane prepolymer U3 was used as the hydroxyl group-terminated urethane prepolymer. The amount of hardener (Coronate L, Tosoh Corporation product name) used was changed to 1.5 parts by mass. Except for this, an adhesive was produced in the same manner as in Example 1. The ethylene oxide unit content in the resulting adhesive was 20 mass %. [Example 4]

[0114] As shown in Table 3, urethane prepolymer U4 was used as the hydroxyl group-terminated urethane prepolymer. The amount of hardener (Coronate L, Tosoh Corporation product name) used was changed to 1.5 parts by mass. Except for this, a pressure-sensitive adhesive was produced in the same manner as in Example 1. The ethylene oxide unit content in the resulting pressure-sensitive adhesive was 38 mass %. [Example 5] As shown in Table 3, an adhesive was produced in the same manner as in Example 3, except that 4 parts by mass of Duranate E-402-80B (product name of Asahi Kasei Corporation) was used instead of the curing agent Coronate L. The ethylene oxide unit content in the obtained adhesive was 20% by mass.

[0115] [Table 2]

[0116] [Table 3]

[0117] In Table 2, the blend amounts of polymer, diisocyanate compound, and catalyst are shown in parts by mass. Also, "isocyanate index" is the value obtained by dividing the number of moles of isocyanate groups of the diisocyanate compound used in producing the hydroxyl-terminated urethane prepolymer by the total number of moles of hydroxyl groups of the oxyalkylene polymer and multiplying the result by 100, and "EO unit content" is the mass ratio (unit: mass%) of ethylene oxide units in the hydroxyl-terminated urethane prepolymer. "-" indicates that the component is not blended. In Table 3, the amounts of urethane prepolymer and curing agent are shown in parts by mass. "EO unit content" is the ratio of ethylene oxide units in the adhesive (unit: mass%). "-" indicates that the component is not included.

[0118] [Adhesive property evaluation] The adhesives of Examples 1 to 5 were evaluated for moisture permeability, adhesive strength to phenolic resin, adhesive strength to human skin, difference between adhesive strength to phenolic resin and adhesive strength to human skin, and storage modulus. The results are shown in Table 3. Unless otherwise specified, test pieces were prepared by cutting the patch to a width of 15 mm and a length of 60 mm so that the flow direction of the original roll was the long side (MD direction). In addition, the carrier and release body were peeled off from the patch and measurements were performed.

[0119] <Moisture permeability> Moisture permeability is the rate at which water vapor passes through a test piece in 24 hours (1 day) 2 The mass was calculated as the unit mass. 100 parts by mass of the produced urethane prepolymer and a curing agent (Coronate L (product name of Tosoh Corporation) or Duranate E402-80B (product name of Asahi Kasei Corporation)) were mixed uniformly in the amounts shown in Table 3, degassed, and applied to a polyester film (release body, thickness 50 μm) that had been subjected to a release treatment using a knife coater so that the dry film thickness was 25 μm, and then cured and dried at 100 ° C for 3 minutes to form an adhesive layer on the release body. A coarse nylon net that does not affect the moisture permeability of the adhesive was attached on the obtained adhesive layer, and then the mixture was stored in a hot air dryer in an atmosphere of 50 ° C for 3 days to complete the crosslinking reaction of the adhesive layer, and the release body was peeled off to prepare a test piece. The moisture permeability is measured by measuring the mass (g) of water vapor passing through the test specimen in 24 hours (1 day) when the relative humidity of one side of the space separated by the test specimen is 90% in an atmosphere of 40°C and the other side of the space is kept dry with a moisture absorbent. 2 The moisture permeability was calculated by converting it to a value per unit. Measurements were performed according to the JIS Z 0208:1976 moisture-proof packaging material moisture permeability test method (cup method), and a circular test piece with a diameter about 10 mm larger than the inside diameter of the cup was placed over a cup containing about 50 g of calcium chloride moisture absorbent, and then a rubber packing and ring were placed over the test piece and screwed in place to prevent it from slipping. After measuring the total mass of this test piece, it was placed in a constant temperature and humidity chamber at 40°C and 90% RH, and the change in mass was measured at regular intervals, and the moisture permeability was calculated according to the following formula. Moisture permeability (g / m 2 ·day)=W×240000 / S In the formula, S is the moisture permeability area (cm 2 ) and W represents the mass increase per hour (g / hr). The moisture permeability was evaluated according to the following criteria. A··5000g / m 2 ·day or more B··4000g / m 2 ·day or more 5000g / m 2 Less than a day C··3000g / m 2 ·day or more 4000g / m 2 Less than a day D···3000g / m 2Less than a day The column "Moisture permeability" in Table 3 shows the calculated moisture permeability and the evaluation results of moisture permeability.

[0120] <Adhesive strength to phenolic resin> According to the test method described in "10. Adhesive strength" of the JIS Z 0237:2009 adhesive tape and adhesive sheet test method, a 15 mm wide test piece was attached to a Bakelite panel (phenolic resin plate, manufactured by Sumitomo Bakelite Co., Ltd., PL-1102) in an atmosphere of 25°C, and pressed once back and forth at a speed of 300 mm / min with a 2 kg rubber roll. After leaving it for 20 minutes, the peel force was measured at a peel angle of 90 degrees or 180 degrees and a peel speed of 300 mm / min. The adhesive strength to phenolic resin was evaluated according to the following evaluation criteria. A...3.0N / 15mm or more B: 2.5N / 15mm or more, less than 3.0N / 15mm C: 2.0N / 15mm or more, less than 2.5N / 15mm D: Less than 2.0N / 15mm The column "Adhesion to phenolic resin" in Table 3 shows the measured adhesion to phenolic resin and the evaluation results of adhesion to phenolic resin.

[0121] <Adhesion to human skin> The adhesive strength of the adhesive to the phenolic resin was measured using the back of a human hand instead of the Bakelite panel. The back of the human hand was degreased with isopropyl alcohol and air-dried before use. The adhesive strength to human skin was evaluated according to the following criteria. A 0.2~1.0N / 15mm D: Less than 0.2N / 15mm or more than 1.0N / 15mm The column "Adhesion to skin" in Table 3 shows the measured adhesion to human skin and the evaluation results of the adhesion to human skin.

[0122] <Difference in adhesive strength between phenolic resin and human skin> The difference in adhesive strength between the phenolic resin and the human skin was calculated using the following formula. "Difference between adhesive strength to phenolic resin and adhesive strength to human skin" = "Adhesive strength to phenolic resin" - "Adhesive strength to human skin" The difference in adhesion to phenol and to human skin was evaluated according to the following criteria. A...2.5N / 15mm or more B: 2.0N / 15mm or more and less than 2.5N / 15mm C: 1.5N / 15mm or more, less than 2.0N / 15mm D: Less than 1.5N / 15mm The column "difference in adhesive strength" in Table 3 shows the evaluation results of the calculated difference in adhesive strength between phenol resin and human skin, and the difference in adhesive strength between phenol and human skin.

[0123] <Storage modulus> 100 parts by mass of the produced urethane prepolymer and a curing agent (Coronate L (product name of Tosoh Corporation) or Duranate E402-80B (product name of Asahi Kasei Corporation)) were used in the amounts shown in Table 3, mixed uniformly, degassed, and applied to a polyester film (release body, thickness 50 μm) that had been subjected to a release treatment using a knife coater so that the dry film thickness was 25 μm, and then cured and dried at 100 ° C for 3 minutes to form an adhesive layer on the release body. A release body was attached onto the obtained adhesive layer, and then stored in a hot air dryer under an atmosphere of 50 ° C for 3 days to complete the crosslinking reaction of the adhesive layer. The release body was peeled off and rolled into a cylindrical shape with a diameter of about 3 mm and a length of 4 cm, with a size of 4 cm wide x 30 cm long, to prepare a test sample. The storage modulus E' is the value obtained by measuring the storage modulus E' (Pa) of the obtained test sample under a strain of 1% under the following measurement conditions. The storage moduli at 25° C. and 80° C. are shown in Table 3. Measurement equipment: Dynamic viscoelasticity measuring equipment (EXSTAR 6000 DMS 6100, Seiko Instruments Inc. product name) Mode: Tensile mode Temperature range: -80~130℃ Heating rate: 3℃ / min Measurement frequency: 1Hz

[0124] [Results explanation] In Table 3, Examples 2 to 5 correspond to examples of the present invention, and Example 1 corresponds to a comparative example of the present invention. If the moisture permeability is rated as A, B or C, the pressure-sensitive adhesive has excellent moisture permeability. If the adhesive strength to phenolic resin is rated A, B or C, the adhesive strength to skin is rated A, and the adhesive strength difference is rated A, B or C, then low adhesion to skin and high adhesion to the substrate are both achieved. Therefore, the adhesives of Examples 2 to 5 have excellent moisture permeability and are able to achieve both low adhesion to the skin and high adhesion to the substrate. In contrast, the adhesive of Example 1 has low moisture permeability and low adhesion to the skin. This is believed to be due to the low EO unit content and low polarity of the adhesive. [Industrial Applicability]

[0125] Adhesives using the urethane prepolymer of the present invention have excellent moisture permeability, as well as low adhesion to the skin and high adhesion to substrates, and therefore can be particularly preferably used as adhesives for attaching various wearable devices. The entire contents of the specification, claims, drawings and abstract of Japanese Patent Application No. 2019-036306, filed on February 28, 2019, are hereby incorporated by reference as the disclosure of the specification of the present invention.

Claims

1. A hydroxyl-terminated urethane prepolymer obtained by reacting an oxyalkylene polymer A having an average number of hydroxyl groups per molecule of 2.1 to 3, an oxyalkylene polymer B having a hydroxyl group per molecule of 1, and a diisocyanate compound, The number average molecular weight of the oxyalkylene polymer B is 8,000 or more, The hydroxyl-terminated urethane prepolymer has an ethylene oxide unit content of more than 10 mass%.

2. 2. The hydroxyl-terminated urethane prepolymer according to claim 1, wherein the oxyalkylene polymer A comprises an oxyalkylene polymer a having 3 hydroxyl groups per molecule and an oxyalkylene polymer b having 2 hydroxyl groups per molecule.

3. 3. The hydroxyl group-terminated urethane prepolymer according to claim 2, wherein the oxyalkylene polymer a has an ethylene oxide unit content of 15 mass% or more.

4. The hydroxyl-terminated urethane prepolymer according to any one of claims 1 to 3, wherein the average number of hydroxyl groups is less than 3.

0.

5. The hydroxyl-terminated urethane prepolymer according to any one of claims 1 to 4, wherein the ethylene oxide unit content in the hydroxyl-terminated urethane prepolymer is 12 to 50 mass%.

6. A pressure-sensitive adhesive obtained by reacting the hydroxyl-terminated urethane prepolymer according to any one of claims 1 to 5 with a curing agent containing a polyisocyanate compound having three or more isocyanate groups in one molecule, The pressure-sensitive adhesive has an ethylene oxide unit content of 10% by mass or more.

Citation Information

Patent Citations

  • Repairing of on line hot rolling slab

    JP1979057446A

  • Urethane prepolymer and two-liquid type urethane adhesive using the same

    JP2016204466A

  • Two-liquid type urethane adhesive

    JP2016204467A

  • Urethane prepolymer, and two-liquid type urethane adhesive using the same

    JP2016204468A

  • Curable composition

    JP2017082113A

Cited By

  • Urethane prepolymer, adhesive, patch, adhesive tape, wearable device and wearable device kit

    JP2024103531A